The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/hmg/ddt057
|View full text |Cite
|
Sign up to set email alerts
|

Atp13a2-deficient mice exhibit neuronal ceroid lipofuscinosis, limited α-synuclein accumulation and age-dependent sensorimotor deficits

Abstract: Mutations in ATP13A2 (PARK9), encoding a lysosomal P-type ATPase, are associated with both Kufor-Rakeb syndrome (KRS) and neuronal ceroid lipofuscinosis (NCL). KRS has recently been classified as a rare genetic form of Parkinson's disease (PD), whereas NCL is a lysosomal storage disorder. Although the transport activity of ATP13A2 has not been defined, in vitro studies show that its loss compromises lysosomal function, which in turn is thought to cause neuronal degeneration. To understand the role of ATP13A2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 82 publications
3
122
1
Order By: Relevance
“…2013) and recently in Atp13a2‐deficient (CLN12) mice (Schultheis et al. 2013). α ‐Synuclein is known to modulate synaptic pathology in mice, at least in part through interactions with another synaptic protein, CSP‐ α (Chandra et al.…”
Section: Discussionmentioning
confidence: 99%
“…2013) and recently in Atp13a2‐deficient (CLN12) mice (Schultheis et al. 2013). α ‐Synuclein is known to modulate synaptic pathology in mice, at least in part through interactions with another synaptic protein, CSP‐ α (Chandra et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PARK9 expression levels were increased in postmortem brains from sporadic PD patients (Ramirez et al, 2006;Ramonet et al, 2012). Studies in cultured neurons also demonstrated that transiently expressed wild-type PARK9 localized to acidic vesicles (Ramirez et al, 2006;Tan et al, 2011;Ramonet et al, 2012). We and others have shown that depletion of PARK9 causes lysosomal dysfunction, accumulation of ␣-syn (Dehay et al, 2012;Usenovic et al, 2012a), and increased sensitivity to zinc .…”
Section: Introductionmentioning
confidence: 90%
“…Initial studies revealed that overexpression of PARK9 reduced the toxicity of ␣-synuclein (␣-syn) in yeast cells and rat primary dopaminergic neurons (Gitler et al, 2009). In addition, PARK9 expression levels were increased in postmortem brains from sporadic PD patients (Ramirez et al, 2006;Ramonet et al, 2012). Studies in cultured neurons also demonstrated that transiently expressed wild-type PARK9 localized to acidic vesicles (Ramirez et al, 2006;Tan et al, 2011;Ramonet et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations